ANALISIS POTENSI DAN REALISASI PENERIMAAN PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH PADA BADAN PENDAPATAN DAERAH KOTA BITUNG - Binangga, Victor E.; Morasa, Jenny Morasa; Pinatik, Sherly (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
Regional Original Income is a reflection of the independence of an area in which there is a Regional Tax and one of them is the hotel tax. This research was conducted to determine the potential and realization of hotel tax revenue on Regional Original Revenue at the Bitung City Regional Revenue Agency. This type of research is qualitative research. The data obtained by using the method of observation, interviews and documentation. The data analysis method used is descriptive analysis method, namely collecting data, analyzing data and drawing conclusions. The results obtained based on the details of the target and realization of Regional Original Revenue in 2017-2020 the percentage of the target and realization of Bitung City's Regional Original Income fluctuated and the largest was in 2019 which was 114.29%. The percentage of the target and realization of the Bitung City hotel tax in 2017 was 96.55%, increased in 2018 by 131.34%, again decreased in 2019 by 118.13% and in 2020 the impact of the Covid-19 pandemic decreased to by 63.07%. Based on the calculation of hotel tax realization data for 2017-2020, the potential hotel tax in Bitung City in 2021 is IDR 781,368,031.00.